The Structure and Function of the Na,K-ATPase Isoforms in Health and Disease - Clausen, Michael V.; Hilbers, Florian; Poulsen, Hanne (Frontiers in Physiology, 2017)
The sodium and potassium gradients across the plasma membrane are used by animal cells for numerous processes, and the range of demands requires that the responsible ion pump, the Na,K-ATPase, can be fine-tuned to the different cellular needs. Therefore, several isoforms are expressed of each of the three subunits that make a Na,K-ATPase, the alpha, beta and FXYD subunits. This review summarizes the various roles and expression patterns of the Na,K-ATPase subunit isoforms and maps the sequence variations to compare the differences structurally. Mutations in the Na,K-ATPase genes encoding alpha subunit isoforms have severe physiological consequences, causing very distinct, often neurological diseases. The differences in the pathophysiological effects of mutations further underline how the kinetic parameters, regulation and proteomic interactions of the Na,K-ATPase isoforms are optimized for the individual cellular needs.